Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja dengan Motivasi Sebagai Variabel Intervening pada PT. Mentari Books - Setiawan, Dwinanto; Fathorrahman, Fathorrahman; Pradiani, Theresia (Policy, Law and Political Research Center, 2025)
This study aims to examine the effect of employee performance through training and work discipline, with motivation as an intervening variable, at PT Mentari Books Indonesia, particularly in the context of intense competition in the publishing and education industries in Indonesia. The sampling method used in this research is a saturated sampling technique or census, in which all 58 marketing employees at PT Mentari Books Indonesia were included as the study sample. This study employs a quantitative research method, with data analysis conducted using path analysis. The results indicate that training and motivation do not have a significant direct effect on the performance of marketing employees at PT Mentari Books Indonesia. However, work discipline has a significant positive effect on performance. Furthermore, motivation is found to mediate the relationship between training and work discipline on employee performance. The theoretical implication of these findings contributes to the strengthening of work motivation theory, particularly within the framework of organizational variable relationships. From a practical standpoint, the company should evaluate the effectiveness of its existing programs to enhance employee performance outcomes.